2016
DOI: 10.5539/jmr.v8n4p118
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Lagrange Interpolation at Sinc Points Error Estimation and Lebesgue Constant

Abstract: This paper gives an explicit construction of multivariate Lagrange interpolation at Sinc points. A nested operator formula for Lagrange interpolation over an m-dimensional region is introduced. For the nested Lagrange interpolation, a proof of the upper bound of the error is given showing that the error has an exponentially decaying behavior. For the uniform convergence the growth of the associated norms of the interpolation operator, i.e., the Lebesgue constant has to be taken into consideration. It turns out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…It is also optimal in the sense of the Lebesgue measure achieving an optimal value less than Chebyshev approximations [23]. We also note that this behavior is found also in bi-variate approximations based on Poly-Sinc methods [24][25][26].…”
Section: Definition 1 Domain and Conditionssupporting
confidence: 53%
“…It is also optimal in the sense of the Lebesgue measure achieving an optimal value less than Chebyshev approximations [23]. We also note that this behavior is found also in bi-variate approximations based on Poly-Sinc methods [24][25][26].…”
Section: Definition 1 Domain and Conditionssupporting
confidence: 53%
“…In [19] it was proved that such interpolation points deliver an accuracy similar to the classical Sinc approximation. The stability of Lagrange approximation at Sinc points is studied in [3,5]. The sequence of Sinc points is generated using a conformal map that redistributes the infinite equidistant points on the real line to a finite interval.…”
Section: Poly-sinc Collocation Methodsmentioning
confidence: 99%
“…where, C 1 , C 2 and C 3 are three positive constants, independent of N . For the stability of such approximation, an upper bound of Lebesgue constant has been discussed in [5]. It was shown that Lebesgue's constant for (7) is following the logarithmic relation,…”
Section: Poly-sinc Collocation Methodsmentioning
confidence: 99%
See 2 more Smart Citations